CRISPR/Cas9 uPAR Gene Knockout Results in Tumor Growth Inhibition, EGFR Downregulation and Induction of Stemness Markers in Melanoma and Colon Carcinoma Cell Lines - Biagioni, Alessio; Chillà, Anastasia; Del Rosso, Mario; Fibbi, Gabriella; Scavone, Francesca; Andreucci, Elena; Peppicelli, Silvia; Bianchini, Francesca; Calorini, Lido; Li Santi, Anna; Ragno, Pia; Margheri, Francesca; et al. (Frontiers in Oncology, 2021)
uPAR is a globular protein, tethered to the cell membrane by a GPI-anchor involved in several cancer-related properties and its overexpression commonly correlates with poor prognosis and metastasis. We investigated the consequences of uPAR irreversible loss in human melanoma and colon cancer cell lines, knocking out its expression by CRISPR/Cas9. We analyzed through flow cytometry, western blotting and qPCR, the modulation of the most known cancer stem cells-associated genes and the EGFR while we observed the proliferation rate exploiting 2D and 3D cellular models. We also generated uPAR “rescue” expression cell lines as well as we promoted the expression of only its 3’UTR to demonstrate the involvement of uPAR mRNA in tumor progression. Knocking out PLAUR, uPAR-encoding gene, we observed an inhibited growth ratio unexpectedly coupled with a significant percentage of cells acquiring a stem-like phenotype. In vivo experiments demonstrated that uPAR loss completely abrogates tumorigenesis despite the gained stem-like profile. Nonetheless, we proved that the reintroduction of the 3’UTR of PLAUR gene was sufficient to restore the wild-type status validating the hypothesis that such a region may act as a “molecular sponge”. In particular miR146a, by binding PLAUR 3’ UTR region might be responsible for uPAR-dependent inhibition of EGFR expression.